Testing models and model transformations using classifying terms. - Hilken, Frank; Gogolla, Martin; Burgueño-Caballero, Lola; Vallecillo-Moreno, Antonio Jesús (My University, 2016)
This paper proposes the use of equivalence partitioning techniques for testing models and model transformations. In particular, we introduce the concept of classifying terms, which are general OCL terms on a class model enriched with OCL constraints. Classifying terms permit defining equivalence classes, in particular for partitioning the source and target model spaces of the transformation, defining for each class a set of equivalent models with regard to the transformation. Using these classes, a model validator tool is able to automatically construct object models for each class, which constitute relevant test cases for the transformation. We show how this approach of guiding the construction of test cases in an orderly, systematic and efficient manner can be effectively used in combination with Tracts for testing both directional and bidirectional model transformations and for analyzing their behavior.
Keywords: Soporte lógico de sistemas; Model transformations; Contract-based specifications; Equivalence partitioning